Retapamulin: a semisynthetic pleuromutilin compound for topical treatment of skin infections in adults and children. (December 2007) - Jacobs, Michael R
Retapamulin is a semisynthetic pleuromutilin compound with in  vitro activity against Gram-positive bacteria, no cross-resistance to other classes of antimicrobial agents in current use and a low potential for development of resistance. A 1% ointment formulation has been developed for clinical use, and a placebo-controlled trial of impetigo in 210  patients produced significantly higher rates of clinical and microbiological success compared with placebo –– 85.6 versus 52.1% and 91.2 versus 50.9%, respectively. Additional comparative studies in over 1900 patients showed noninferiority to topical fusidic acid and oral cephalexin and a low frequency of adverse events. In 2007, retapamulin was approved in the USA for topical treatment of impetigo caused by Streptococcus pyogenes and methicillin-susceptible Staphylococcus aureus, and in the EU for topical treatment of impetigo and infected wounds caused by S.  pyogenes and S.  aureus, with approvals including adults and children over 9 months of age.